On Human and Class Character of Morals - Kapačiauskienė, Danutė (Problemos, 1976)
A functional interpretation of morals is suggested by the author: human or class character of morals conveys the peculiarities of its social function. Human character of morals consists in its ability to appraise a person as such, independently of his social status. Class character of morals is conditioned by class and social relations under which moral appraisal of people’s behaviour is influenced by their different status. Therefore, only the morals of the classless communist society can be common to all mankind whereas that of the class society can be common only to an extent to which moral appraisal of a person irrespective of his social status is possible.